The kindness of dying and the fear of euthanasia - Velásquez Prada, Patricia (2023)
An approach to the right to die with dignity, a good death and the arguments on which disobedience to the ethics of the sanctity of life is raised. In short, the right to euthanasia as the foundation of the right to life itself, leads to the reflection around the need to propose legislation where the principle of compassion towards the suffering of the convalescent person is extended to certain conditions related to health. that require a compassionate attitude, that grants the right to consider psychic pain, as well as physical pain, allow people with an unbearable and intense psyche condition to access the same right that is assumed in a terminal physical illness.